Steps towards printed electronics on silicone rubber for active implantable medical devices (AIMD) (Transactions on Additive Manufacturing Meets Medicine, 2024)
We report the current state of the art and novel approaches in additive manufacturing AIMD devices including electrodes, wires and electronics in silicone rubber encasements.
Keywords: Silicone; biocompatible electric leads